The Effectiveness of Using Learning Video Media on Student Learning Outcomes in Economics at SMAN 5 Pekanbaru - Putri Salwa Amalina; Mujiono Mujiono; Hendripides Hendripides (CV. Rayyan Dwi Bharata, 2023)
This study aims to determine the effectiveness of using learning video media on student learning outcomes in economics at SMAN 5 Pekanbaru. The sample of this research is 74 students obtained from purposive sampling technique. This research uses experimental method. Instruments for collecting data are student activity assessment sheets and tests. After the data was analyzed, it was obtained that the use of instructional video media was categorized as very good with a percentage of 77.03% and learning outcomes were categorized as good with an average learning result of 89.59. After the data were analyzed using the Paired Sample Test, it was found that the sig (2-tailed) value was 0.000 0.05, so it was concluded that there was a difference in the average pre-test and post-test scores. The calculated t value is negative, which is -9.017, which means that the pre-test value is lower than the post-test. To measure the level of effectiveness using the normalized gain test, an average gain value of 60.74 is obtained, which means that the use of instructional video media is quite effective in improving student learning outcomes.